Peak blood lactate parameters in athletes of different running events during low-intensity recovery after ramp-type protocol - Vucetic, V.; Mozek, M.; Rakovac, M. (The Journal of Strength and Conditioning Research, 2015)
The aims of this study were to explore the differences in the peak blood lactate concentration (Lapeak) and time to reach Lapeak during low-intensity recovery after an all-out treadmill ramp test in runners of 4 diverse running disciplines and different training regimes and to identify the most opportune sampling time to determine Lapeak in these athlete groups. The participants were 48 Croatian national-level male track runners (10 sprinters [S], fifteen 400-m runners [S4], 10 middle-distance [MD] runners and 13 long-distance [LD] runners). The runners performed an incremental treadmill protocol until volitional exhaustion, with the inclination of 1.5%, and speed increments of 1 km/h every 60 seconds. During recovery, they walked at 5 km/h for 5 minutes. Fingertip capillary blood samples were collected at the end of the first, third, and fifth minute of recovery. Peak blood lactate concentration in LD was significantly lower than in runners of other disciplines (10.9 ± 2.4 mmol/L for LD; 13.7 ± 2.9 for MD; 14.0 ± 1.4 for S4; 15.1 ± 2.7 for S) (p < 0.01). No significant difference was observed among other groups. There was no significant difference in tLapeak among the 4 participant groups. In conclusion, LD had a significantly lower Lapeak in comparison to other runners; runners of all disciplines reached Lapeak within the first 2 minutes of recovery.